2020
DOI: 10.1101/2020.05.30.125138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SHP2 Inhibition Abrogates Adaptive Resistance to KRASG12C-Inhibition and Remodels the Tumor Microenvironment ofKRAS-Mutant Tumors

Abstract: KRAS is the most frequently mutated oncogene in human cancer, and KRAS inhibition has been a longtime therapeutic goal. Recently, inhibitors (G12C-Is) that bind KRASG12C-GDP and react with Cys-12 were developed. Using new affinity reagents to monitor KRASG12C activation and inhibitor engagement, we found that, reflecting its action upstream of SOS1/2, SHP2 inhibitors (SHP2-Is) increased KRAS-GDP occupancy, enhancing G12C-I efficacy. SHP2-Is abrogated feedback signaling by multiple RTKs and blocked adaptive res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Several mechanisms have been proposed to explain the acquired resistance to KRASG12C inhibitors. Fedele et al [125] found that G12C evokes adaptive resistance in vitro and in vivo by inducing KRASG12C re-activation. Ryan et.…”
Section: Correlation Between Genetic Profile and Tumor Stagingmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the acquired resistance to KRASG12C inhibitors. Fedele et al [125] found that G12C evokes adaptive resistance in vitro and in vivo by inducing KRASG12C re-activation. Ryan et.…”
Section: Correlation Between Genetic Profile and Tumor Stagingmentioning
confidence: 99%
“…SHP2 inhibition (SHP2i) blunts GAB1-GRB2-SOS1 complex formation assembled by RTKs, thus interfering with RAS-GTP loading and activation [141]. Increased RAS-GDP occupancy provides a unique vulnerability to KRAS-GDP bound G12Ci, and complete engagement of KRAS G12C by ARS-1620 was observed in 1 hour compared to about 70% basal engagement rate in cells [142]. SHP2i enhances the efficacy of G12Ci, exacerbates MAPK suppression and overcomes G12Ci resistance in various cancers [33,112,118,[143][144][145][146].…”
Section: Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…Overall, the primary oncogenic role of the SHP2 in the activation of the RAS/Raf pathway is to cause dephosphorylation of the tyrosine residues in the scaffolding proteins that result in the increased conversion of inactive RAS (RAS-GDP) to the activated RAS (RAS-GTP) [ 53 ]. This catalytic function also makes SHP2 a critical facilitator in acquired resistance of the RAS signaling reactivation, to overcome pharmacological inhibition [ 54 ]. These properties promote SHP2 inhibition as an attractive way to combat adaptive resistance, both as a monotherapy as well as and in combination with other agents such as, MEK inhibitors.…”
Section: Targeting Krasmentioning
confidence: 99%